Private and Public Schooling The Experience of Rural Punjab in School Education - Toor, Kamalpreet Kaur (JOURNAL OF INDIAN EDUCATION, 2023)
Present study qualitatively analyses some of the critical issues of the rising demand of private school education in Punjab more specifically among rural community. Focus group discussions are administered with teacher activists and educational administrators to generate data. After thematic analysis six major themes such as quality education and infrastructure facilities, attractive propaganda of private schools, insecurities of parents due to agrarian crises, English as medium of instruction, ostentatious culture, and deterioration of the status of government school teachers have emerged that all collaboratively accelerate mushrooming of private schools in rural areas of Punjab.